2000
DOI: 10.1002/1097-0096(200011/12)28:9<469::aid-jcu4>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically guided percutaneous treatment of hepatic hydatid cysts: Long‐term results

Abstract: Purpose. The purpose of this study was to evaluate the safety and efficacy of sonographically guided percutaneous drainage and irrigation of hepatic hydatid cysts.Methods. Sixty-one patients with 84 hepatic hydatid cysts were treated using the puncture, aspiration, injection, and reaspiration (PAIR) technique under sonographic guidance. Patients with cysts larger than 6 cm in diameter underwent PAIR followed by percutaneous drainage (PAIR-PD). The cysts were sterilized by the injection of 1 of 2 scolicidal age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
3
10
0
1
Order By: Relevance
“…Successful percutaneous treatment of hydatid liver disease with scolicidal agents also has been reported. 2,3,5,[7][8][9]19,21 Recently, results of medical treatment with albendazole and mebendazole have been reported. [22][23][24] Benzimidazole derivatives (flubendazole, albendazole, and mebendazole) are commonly used for the treatment of hydatid disease in high-risk patients, to prevent secondary hydatidosis, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful percutaneous treatment of hydatid liver disease with scolicidal agents also has been reported. 2,3,5,[7][8][9]19,21 Recently, results of medical treatment with albendazole and mebendazole have been reported. [22][23][24] Benzimidazole derivatives (flubendazole, albendazole, and mebendazole) are commonly used for the treatment of hydatid disease in high-risk patients, to prevent secondary hydatidosis, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of sclerosing agents, such as cetrimonium bromide, hypertonic saline, hydrogen peroxide, alcohol, and silver nitrate, are commonly used for percutaneous treatment of hepatic hydatid cysts. 2,[5][6][7][8][9] Scolicidal solutions (e.g., formalin and hypertonic saline) have toxic effects on the biliary tree. [10][11][12] Benzimidazole derivatives (albendazole and mebendazole) are the most preferred chemotherapeutic agents, although the efficacy of systemic administration is limited.…”
mentioning
confidence: 99%
“…Over the last decade there has been growing evidence that percutaneous treatment of uncomplicated hydatid liver disease may be a valid alternative to surgery, because it offers an effective and inexpensive therapeutic tool, particularly in those regions where the disease is endemic and medical resources are limited. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Two recent randomized trials by Khuroo et al 22,23 showed that percutaneous treatment of HLCs proved to be a superior form of medical treatment when used with albendazole and proved as effective as open surgical drainage but at a lower cost and with a more reduced complication rate than surgery. Our long-term experience with D-PAI confirms the good results in terms of the feasibility and effectiveness of this ultrasonographically guided interventional procedure, in keeping with the findings of other authors.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most relevant questions about the long-term efficacy and safety of percutaneous treatment have been addressed by recent studies [24][25][26] in which no case of either spillage of the echinococci into the abdomen or intrahepatic or extrahepatic diffusion of the hydatid disease was reported. The involutional changes after percutaneous treatment appeared stable during the follow-up period, with a mean observation time of 19 to 37 months (range, 1-72 months).…”
mentioning
confidence: 99%
“…Allergic symptoms may indeed occur during this procedure and several instances of anaphylactic shock have been observed, with a few fatalities; they are, however, less frequent than during surgical operations. In a recent published series of 84 hepatic cysts punctured in 61 patients, 5 developed urticaria and 2 an anaphylactic reaction that was successfully treated (90).…”
Section: Cyst Puncture and Anaphylaxis In Cystic Echinococcosismentioning
confidence: 99%